The relationship between community structural characteristics, the context of crack use and HIV risk behaviors in San Salvador, El Salvador - Dickson-Gomez, Julia (2012)
This paper explores community structural factors in different low-income communities in the San Salvador, El Salvador that account for differences in the social context in which crack is used and in the HIV risk behaviors among crack users. Results suggest that both more distal (type of low-income community, level of violent crime and poverty) and proximate structural factors (type of site where drugs are used, and whether drugs are used within or outside of community of residence) influence HIV risk behaviors among drug users. Additionally, our results suggest that community structural factors influence the historical and geographic variation in drug use sites.